Analisis Pengaruh Jumlah Kantor Bank, Rata-Rata Gaji, dan Beban Overhead Terhadap Profitabilitas Bank - Fakaruzzaman Hidayatullah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Banking competition consists of price and non-price competition. Price competition from credit and interest rate deposits while non-price competition from the quantity and quality of bank services. Quality of service is subjective, so in this study using the quantity of services. Measured quantity of bank services from a variety of services provided to customers is calculated by unit or the amount of funds expended. This study examines the effect of the quantity of services to bank profitability. Bank profitability measured by ROA. Quantity of services consists of a number of bank offices, the number of ATM machines, overhead expenses and average salary. The results showed that the number of bank offices and the average salary of a significant positive effect on the profitability of banks, while the overhead burden of significant negative effect on the profitability of banks. The three variables simultaneously have a positive effect on bank profitability.